Active engine mounting controller design using linear quadratic regulator and proportional integral derivative - Mahil, M. mahil; Ahmad Shah, Muzzaffar; Faris, Waleed Fekry (Inderscience Publishers, 2011)
Design and implementation of proportional integral derivative (PID) and linear quadratic regulator (LQR) controllers to attenuate the engine-body disturbance is presented in this paper. These control techniques are implemented on two degree of freedom engine-body vibration model so that vibration isolation is achieved by controlling the actuator force placed between two engine mounts which rejects the disturbance so as to minimise the vibration in the vehicle body and passenger cabin. Comparison is done between PID and LQR which reflects their performances on our engine vibration model